Extraction of building outline using LiDAR datasets / Muhamad Akmal Hilmi - Hilmi, Muhamad Akmal (2022)
LiDAR is a new tool that can provide very precise, accurate and high-resolution images of the surface of the earth, vegetation and environment. LiDAR uses a laser range which is mounted in a navigated aircraft to scan earth surface at very high rates and collect very dense cloud which has x y and z coordinates. In this study, building outline is extracted using LiDAR dataset. The study area is located at Presint 11, Putrajaya and the survey area is 1 km x 1 km per square. There were 43 check points collected. The points must be well defined. For accuracy assessment, there are 2 types of accuracy assessment. For quantitative assessment, the RMSE (x,y) between LiDAR data and aerial photos. For qualitative assessment, the orthophoto is overlay with LiDAR DSM. The accuracy result for both data are within tolerance under 2.5 m for class 1 with scale of 1: 10,000 according to ASPRS 2014. This research provides new and important information to the currently limited knowledge of the utility of LiDAR.